Acid Sphingomyelinase Is a Modulator of Contextual Fear - Zoicas, Iulia; Kornhuber, Johannes (International Journal of Molecular Sciences, 2022)
Acid sphingomyelinase (ASM) regulates a variety of physiological processes and plays an important role in emotional behavior. The role of ASM in fear-related behavior has not been investigated so far. Using transgenic mice overexpressing ASM (ASMtg) and ASM deficient mice, we studied whether ASM regulates fear learning and expression of cued and contextual fear in a classical fear conditioning paradigm, a model used to investigate specific attributes of post-traumatic stress disorder (PTSD). We show that ASM does not affect fear learning as both ASMtg and ASM deficient mice display unaltered fear conditioning when compared to wild-type littermates. However, ASM regulates the expression of contextual fear in a sex-specific manner. While ASM overexpression enhances the expression of contextual fear in both male and female mice, ASM deficiency reduces the expression of contextual fear specifically in male mice. The expression of cued fear, however, is not regulated by ASM as ASMtg and ASM deficient mice display similar tone-elicited freezing levels. This study shows that ASM modulates the expression of contextual fear but not of cued fear in a sex-specific manner and adds a novel piece of information regarding the involvement of ASM in hippocampal-dependent aversive memory.
CRIS-Team Scopus Importer:2022-04-01
Keywords: ASM; Contextual fear; Cued fear; Fear conditioning; Fear extinction; Fear learning; Knock-out mice; PTSD; Transgenic mice